2022
DOI: 10.1016/j.msard.2022.103563
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple sclerosis-related genes regulated by EBV-encoded microRNAs in B cells

Abstract: Background: Multiple sclerosis (MS) is driven by the interaction between genetic susceptibility and environmental triggers, particularly to Epstein-Barr virus (EBV) infection. EBV-encoded microRNAs (miRNAs) are abundantly expressed in all stages of EBV infection and latency, which can target both viral and host cellular mRNAs, allowing EBV-infected B cells to evade the host immune response. However, it remains a big gap to understand the roles of EBV miRNAs and their target genes in MS pathogenesis.Methods: We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Whereas recent studies demonstrated that the interplay between T and B cells in immune responses participate in the pathogenesis and progression in MS [8] and NMOSD [7]. Many studies have proposed that humoral immune-mediated pathogenesis in MS, for the reasons that the OCB in the CSF, existence of B cell-rich aggregates in the meninges, and effective treatment of CD19/20monoclonals depleting B cells in patients [8,10].Study suggested that CD72 acts as an inhibitory co-receptor of B cells in MG [11],and finding was supporting the hypothesis of B cell activation in the antibody-mediated process of MS [11][12][13].Although MS is primarily mediated by T lymphocytes, there are some evidence that B cells and self-reactive antibodies play a role in the pathogenesis of MS as well [14]. The enhanced un-derstanding of T cell and B cell surface receptors and genes that are involved in the pathogenesis of MG and MS, needs further studies and clinical trials for developing more effective treatment options.…”
Section: Discussionmentioning
confidence: 75%
“…Whereas recent studies demonstrated that the interplay between T and B cells in immune responses participate in the pathogenesis and progression in MS [8] and NMOSD [7]. Many studies have proposed that humoral immune-mediated pathogenesis in MS, for the reasons that the OCB in the CSF, existence of B cell-rich aggregates in the meninges, and effective treatment of CD19/20monoclonals depleting B cells in patients [8,10].Study suggested that CD72 acts as an inhibitory co-receptor of B cells in MG [11],and finding was supporting the hypothesis of B cell activation in the antibody-mediated process of MS [11][12][13].Although MS is primarily mediated by T lymphocytes, there are some evidence that B cells and self-reactive antibodies play a role in the pathogenesis of MS as well [14]. The enhanced un-derstanding of T cell and B cell surface receptors and genes that are involved in the pathogenesis of MG and MS, needs further studies and clinical trials for developing more effective treatment options.…”
Section: Discussionmentioning
confidence: 75%
“…Significantly, such regulators have been recently linked to the pathogenesis of MS. In one study, seven MS susceptibility genes were found to be up-regulated by at least fifteen EBV-derived microRNAs [ 68 ]. All previous findings at the genomic level point to another critical link between EBV infection and the pathogenesis of MS aside from the classic hypothesis [ 17 ].…”
Section: Ebv and The Risk For Ms: Evidence From Genomic Studiesmentioning
confidence: 99%
“…Moreover, intralesional WM-enriched ME group iii (ME19, 13, 8) and ME18 ( Fig2E ) are marked by genes that are primarily expressed by immune cells ( MMP9 , FBP1 , S100A12 , GPNMB , CXCR4 , FigS7A-B ). Interestingly, CXCR4 (a hub gene in MS-related pathways (54)) is pathogenically regulated by Epstein-Barr virus (EBV) infection of B cells (55), which is thought to be in the causal chain of MS (56). Genes involved in lipid storage/catabolism and macrophage differentiation/activation ( CD36 , SLC37A2 , MSR1 , NR1H3 , PLA2G7 ) are differentially enriched in intralesional WM and are primarily expressed by myeloid cells (microglia, monocytes, and macrophages) and γδT cells ( FigS7B ).…”
Section: Mainmentioning
confidence: 99%